PSXII-21 Pregnancy associated glycoproteins for pregnancy diagnosis on day 25 of gestation. (8th October 2021) - Holton, Matthew P; de Melo, Gabriela; Davis, Dylan B; Stewart, R Lawton; Pohler, Ky G; Lamb, G Cliff C; Fontes, Pedro L
Abstract: The objective of this study was to evaluate the use of plasma concentrations of pregnancy associated glycoproteins (PAG) for pregnancy diagnosis in beef cows on day 25 of gestation. Additionally, differences in circulating concentrations of PAG among cows that experienced late embryonic/early fetal mortality (LEM) were evaluated. Beef cows (n = 214) were exposed to the 7-d CO-Synch + CIDR protocol followed by fixed-time artificial insemination (day 0). Blood samples were collected on days 25 and 29 to determine circulating concentrations of PAG and ultrasonography on day 29 was used as the gold-standard method for pregnancy diagnosis. On days 25 and 29, PAG concentrations were greater (P < 0.001) in pregnant compared with non-pregnant cows. Sensitivity, specificity, positive predicted value (PPV), negative predicted value (NPV), and accuracy on day 25 were 87, 80, 83, 84, and 83%, respectively. Sensitivity, specificity, PPV, NPV, and accuracy for PAG on day 29 were 99, 94, 96, 97, and 99%, respectively. Pairwise comparison of receiver operating characteristics curve analysis indicated greater area under the curve for PAG on day 29 compared with day 25 (P < 0.001). There were no differences in plasma concentrations of PAG on day 25 among cows that experienced LEM compared to cows that maintained pregnancy (P = 0.46). Concentrations of PAG on day 29 were reduced (P = 0.03) in cows that experienced LEM compared with cows that maintained pregnancy, and were not different between LEM and non-pregnant cows (P = 0.12). In summary, cows that experienced LEM had decreased plasma concentrations of PAG compared with cows that maintained pregnancy. The PAG assay utilized in this study yielded accurate pregnancy diagnosis results on day 29 of gestation: however, the presence of false negative results (NPV = 84%) limits its use on day 25 of gestation.